MiR-24-3p regulates CDX2 during intestinalization of cardiac-type epithelium in a human model of Barrett's esophagus. Issue 7 (9th February 2021) - Gil-Gómez, Gabriel; Fassan, Matteo; Nonell, Lara; Garrido, Marta; Climent, Marta; Anglada, Roger; Iglesias, Mar; Guzzardo, Vicenza; Borga, Chiara; Grande, Luis; de Bolós, Carme; Pera, Manuel
Summary: Background: Cardiac-type epithelium has been proposed as the precursor of intestinal metaplasia in the development of Barrett's esophagus. Dysregulation of microRNAs (miRNAs) and their effects on CDX2 expression may contribute to intestinalization of cardiac-type epithelium. The aim of this study was to examine the possible effect of specific miRNAs on the regulation of CDX2 in a human model of Barrett's esophagus. Methods: Microdissection of cardiac-type glands was performed in biopsy samples from patients who underwent esophagectomy and developed cardiac-type epithelium in the remnant esophagus. OpenArray™ analysis was used to compare the miRNAs profiling of cardiac-type glands with negative or fully positive CDX2 expression. CDX2 was validated as a miR-24 messenger RNA target by the study of CDX2 expression upon transfection of miRNA mimics and inhibitors in esophageal adenocarcinoma cell lines. The CDX2/miR-24 regulation was finally validated by in situ miRNA/CDX2/MUC2 co-expression analysis in cardiac-type mucosa samples of Barrett's esophagus. Results: CDX2 positive glands were characterized by a unique miRNA profile with a significant downregulation of miR-24-3p, miR-30a-5p, miR-133a-3p, miR-520e-3p, miR-548a-1, miR-597-5p, miR-625-3p, miR-638, miR-1255b-1, and miR-1260a, as well as upregulation of miR-590-5p. miRNA-24-3p was identified as potential regulator of CDX2 gene expression in three databases and confirmed in esophageal adenocarcinoma cell lines. Furthermore, miR-24-3p expression showed a negative correlation with the expression of CDX2 in cardiac-type mucosa samples with different stages of mucosal intestinalization. Conclusion: These results showed that miRNA-24-3p regulates CDX2 expression, and the downregulation of miRNA-24-3p was associated with the acquisition of the intestinal phenotype in esophageal cardiac-type epithelium.